Logos of Phenomenology and Phenomenology of The Logos. Book Two The Human Condition in-the-Unity-of-Everything-there-is-alive Individuation, Self, Person, Self-determination, Freedom, Necessity - Tymieniecka, Anna-Teresa (Analecta Husserliana, The Yearbook of Phenomenological Research, 2006)
The human being is today at the center of scientific, social, ethical and philosophical debates. The Human Condition-in-the-unity-of-everything-there-is-alive, under whose aegis the present selection of essays falls, offers the urgently needed new approach to reinvestigating humanness. While recent advances in the neurosciences, genetics and bio-engineering challenge the traditional abstract conception of "human nature", indicating its transformability, thus putting in question the main tenets of traditional philosophical anthropology, in the new perspective of the Human Creative Condition the human individual is seen in its emergence and unfolding within the dynamic networks of the logos of life, and within the evolution of living types. Just the same, the creative logos of the mind lifts the human person into a sphere of freedom. Within the networks of the logos we retrieve the classical principles - human subject, ego, self, body, soul, person - reinterpret them to counter the naturalistic critique (Tymieniecka). Thus principles of a new philosophical anthropology satisfying the requirements of the present time are laid down.